Farmers’ Vulnerability to Climate Change: A Study in North Himalayan Region of Uttarakhand, India - Raghuvanshi, Rupan; Ansari, M.A. (Indian Journal of Extension Education, 2020)
Erratic, unpredictable and unexpected changes in climate are threatening agriculture productivity as well as livelihood security of rural communities. Climate variability and Climate change can disrupt food supply chain, reduce access to food, and affect food quality. Consequently, vulnerability of farmers, and ipso facto the agriculture production systems, are increasingly stressed which is reflected on various human development indicators of the region. The present study was undertaken to assess farmer’s vulnerability for enhancing location-specific adaptation and mitigation strategies. The study was conducted in Garhwal and Kumaon Division of Uttarakhand, a North Himalayan state of India. Study sample comprised of 200 farmers selected through simple random sampling. A vulnerability index was developed applying principal component analysis of the selected variables. The study findings indicated that majority of the respondents (64%) were found moderately vulnerable to climate change. Further, 71.4 per cent displayed medium level of awareness about climate change, and more than 50 per cent had highly favourable attitude towards climate change. Additionally, more than 90 per cent knew about adaptation practices such as adoption of drought/frost tolerant practices, Change in planting time, diversification from farming to non-farming activities and diversification of crops and varieties. The study has implications for policy makers as well as scientists designing adaptation strategies to minimise the adverse impact of climate change on agriculture in the vulnerable zones of the North Himalayan state in India.
Keywords: Adaptation strategies; Climate change; Climate smart agriculture; Farmers’ vulnerability; Himalayan region; Rural livelihoods